Selective Localization of Shanks to VGLUT1-Positive Excitatory Synapses in the Mouse Hippocampus - Heise, Christopher; Schroeder, Jan C.; Schoen, Michael; Halbedl, Sonja; Reim, Dominik; Woelfle, Sarah; Kreutz, Michael R.; Schmeisser, Michael J.; Boeckers, Tobias M. (Frontiers in Cellular Neuroscience, 2016)
Abstract Members of the Shank family of multidomain proteins (Shank1, Shank2, and Shank3) are core components of the postsynaptic density (PSD) of excitatory synapses. At synaptic sites Shanks serve as scaffolding molecules that cluster neurotransmitter receptors as well as cell adhesion molecules attaching them to the actin cytoskeleton. In this study we investigated the synapse specific localization of Shank1-3 and focused on well-defined synaptic contacts within the hippocampal formation. We found that all three family members are present only at VGLUT1-positive synapses, which is particularly visible at mossy fiber contacts. No costaining was found at VGLUT2-positive contacts indicating that the molecular organization of VGLUT2-associated PSDs diverges from classical VGLUT1-positive excitatory contacts in the hippocampus. In light of SHANK mutations in neuropsychiatric disorders, this study indicates which glutamatergic networks within the hippocampus will be primarily affected by shankopathies.